2020
DOI: 10.1016/j.fas.2019.08.017
|View full text |Cite
|
Sign up to set email alerts
|

How many screws are necessary for subtalar fusion? A retrospective study

Abstract: BACKGROUND Biomechanical studies have shown a higher compressive force and higher torsional stiffness for fixation with three screws compared to two screws. However, clinical data to compare these fixation techniques is still lacking. METHODS A retrospective analysis of 113 patients was performed, who underwent isolated subtalar fusion between January 2006 and April 2018. RESULTS Revision arthrodesis was required in 8% (n=6/36) for 3-screw-fixation and 38% (n=35/77) for 2-screwfixation. For 3-screw-fixation, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The fusion was facilitated by an autologous bone graft from the anterior half of the resected fibula and allograft cancellous bone chip, combined with rigid fixation using 3 headless compression screws. 10 We believe that this favorable fusion environment led to the successful fusion of the subtalar joint, despite the failure of previous hindfoot arthrodesis. A second limitation of this technique is that, when drilling a hole through the nail using a carbide drill bit, the surrounding tissues may be covered with disseminated metal debris.…”
Section: Discussionmentioning
confidence: 90%
“…The fusion was facilitated by an autologous bone graft from the anterior half of the resected fibula and allograft cancellous bone chip, combined with rigid fixation using 3 headless compression screws. 10 We believe that this favorable fusion environment led to the successful fusion of the subtalar joint, despite the failure of previous hindfoot arthrodesis. A second limitation of this technique is that, when drilling a hole through the nail using a carbide drill bit, the surrounding tissues may be covered with disseminated metal debris.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated risk factors for subtalar nonunion to include a prior ankle arthrodesis, as well as an increased body mass index, diabetes mellitus, and neuropathy. 10,18 There has been limited published data on the union rates of a subtalar arthrodesis below an ankle. Zanolli et al 19 undertook 151 subtalar arthrodeses, of which only 13 were below an ankle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated risk factors for subtalar nonunion to include a prior ankle arthrodesis, as well as an increased body mass index, diabetes mellitus, and neuropathy. 10,18…”
Section: Discussionmentioning
confidence: 99%
“…(11) With these growing numbers, pseudarthrosis rates of subtalar fusion procedures are well documented in the literature, with non-union rates ranging from 14-35%. (1,12,13) Utilizing an effective bone graft is a valuable tool in achieving successful arthrodesis, and several categories of bone graft are available to surgeons. ICBG is the gold standard, however limited quantity of autograft bone and relevant co-morbidities with harvesting impact the quantity that a surgeon can obtain.…”
Section: Discussionmentioning
confidence: 99%